2022
DOI: 10.1155/2022/6748684
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Impact of the Development Level of Aerobics Movement on the Public Health of the Whole Population Based on Artificial Intelligence Technology

Abstract: With the enhancement of China’s comprehensive national power and the improvement of people’s living standards, health has become the goal that people pursue. While people are thirsty for extensive knowledge and a healthy body, they also pay more attention to the cultivation of elegant temperament and the enjoyment of beauty, and aerobics has become a hot spot for national fitness with its advantages of coordinated and beautiful movements, bright and cheerful rhythm and obvious fitness effects. Aerobics is a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Among many traditional sports, aerobics is loved by many people because its exercise intensity and movement difficulty are relatively low, it has diverse forms and rich in content, its line effect is remarkable. People with different levels, ages, and gender, can learn it (Ji & Qiu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Among many traditional sports, aerobics is loved by many people because its exercise intensity and movement difficulty are relatively low, it has diverse forms and rich in content, its line effect is remarkable. People with different levels, ages, and gender, can learn it (Ji & Qiu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%